Don’t run, boy! (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Don't Run, Boy! is a theatrical work by Cia Nosso Olhar, a black collective from the city of Florianópolis - SC. The play premiered during the Covid 19 pandemic in an online format. The dramaturgy and the play changed as its presentations took place.. It tells the story of Eduardo da Silva Santos, an 11-year-old black and peripheral boy, who was the target of a stray bullet. The monologue denounces violence against black and peripheral children and criticizes racism and the disproportionate violence used by the armed forces in the outskirts of Brazil, where every 23 minutes a black person is murdered. Currently, the play has had almost 40 performances.
Keywords: anti-racism; black theater; Cia Nosso Olhar; black genocide; racism